Tuberculoma of the Tongue Presenting as Hemimacroglossia - S. P. S. Yadav; Arpit Agrawal; J. S. Gulia; Sunita Singh; Arsh Gupta; Vineet Panchal (Case Reports in Medicine)
The underdiagnosis of extrapulmonary tuberculosis lesions, along with an emerging global resistance to antitubercular drugs, warrants an increased awareness of the involvement of Mycobacterium tuberculosis in atypical lesions of oral cavity. Tongue is the most common site of oral tuberculosis. We report a rare presentation of lingual tuberculosis in a 65-year-old male, a chronic tobacco chewer, who came to us with swelling of the tongue which apparently looked like hemimacroglossia, leading to the clinical diagnosis of submucosal carcinoma of tongue. Enlargement of tongue is a slow process resulting from gradual invasion and lodging of bacilli in the tongue. Biopsy and histopathological examination revealed tuberculous etiology of the lesion and the patient responded well to antitubercular therapy.